Hydro- Chemical Evolution of Palk Strait Region, Bay of Bengal - govindasamy, chinavenkataraman; Arulpriya, Mani; Ruban, Packiasamy; Meenakshi, V. R. (Journal of Tropical Life Science, 2012)
Present analysis was carried out the physico- chemical parameters of two stations such as Thondi and Soliyakudi in the southeast Palk Strait region during the monsoon and post monsoon seasons (November 2008 – March 2009). High temperature (31ËšC) and salinity (35%o) was recorded in the month of March (post monsoon). Dissolved oxygen content was high (5.2 O2 mg. l-1) during in the monsoonal season. Compared with other nutrients such as NO3, NO2 and SiO2, the total phosphorous concentration was high in both the stations during monsoonal season. In general concentrations of all the nutrients were high in the station I during monsoon season (November and December) which could be due to the addition of nutrients through the sewage, agricultural and land run off.